2014
DOI: 10.1108/ijem-01-2012-0017
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of university students regarding transformation in South Africa

Abstract: 2005),"Equal opportunity and affirmative action for South African women: a benefit or barrier?", Women in Management Review, Vol. 20 Iss 1 pp. 56-71 http://dx.Access to this document was granted through an Emerald subscription provided by emerald-srm:368933 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…It is widely acknowledged that higher education programmes in the country reflect no or slow changes in curriculum transformation to be inclusive (Seabi, Seedat, Khoza-Shangase, & Sullivan, 2014 ). Higher education programmes, including SLH programmes in the country, are largely still based on a Eurocentric, Western epistemology with minimal, if any, inclusion of Afrocentric epistemology and ontology.…”
Section: Higher Education Context Lacunaementioning
confidence: 99%
“…It is widely acknowledged that higher education programmes in the country reflect no or slow changes in curriculum transformation to be inclusive (Seabi, Seedat, Khoza-Shangase, & Sullivan, 2014 ). Higher education programmes, including SLH programmes in the country, are largely still based on a Eurocentric, Western epistemology with minimal, if any, inclusion of Afrocentric epistemology and ontology.…”
Section: Higher Education Context Lacunaementioning
confidence: 99%
“…The reasons for protest are manifold, but generally revolve around diversity and transformation, or lack thereof. Despite major government instigated restructurings -the most noticeable being the 2004 merger operation -many university cultures have shown a notorious slow degree of change compared with the pre-1994 situation (Aina 2010;Balintulo 2003;Chetty & Merrett 2014;Cloete 2014;Cross 2004;Higgins 2013;Jansen 2009;Jawitz 2010;Kamsteeg 2011;Keet & Nel 2016;Seabi et al 2012;Soudien 2008;Tabensky & Matthews 2015;Verwey & Quayle 2012;Walker 2005a;2005b;Walker & Loots 2016). This article presents narratives of self-identity of students from the University of the Free State (UFS), a formerly all-white and Afrikaans-medium taught university that is actually going through a critical transition phase (Keet & Nel 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is connected with some identified overarching emerging themes of this study: (1) Supportive academic leadership: in terms of academic modelling and good listeners and communication skills; (2) Teaching and learning quality: in terms of class management, participatory approach to teaching and supportive learning environment; (3) Academic versatility: in terms of lecturers' knowledge diversity. This finding infers that the lecturers' leadership practices in terms of teaching and learning quality and demonstration of academic leadership in the university have helped to transform and improve students' socio-academic abilities which is an expected function of a good academic leader (Balwant, 2016;Dahawy & Elmelegy, 2010;Elmelegy, 2015;Hofmeyer et al, 2015;Seabi et al, 2012;Warhurst, 2006). More so, findings revealed that lecturers' involvement of students in class sessions like questions and answers session and sharing contributions empowered students to become academically curious and inquisitive.…”
Section: Discussionmentioning
confidence: 85%
“…Also, Hofmeyer et al 2015in their qualitative study into the Australian higher education sector found that influence direction, culture, visibility and audibility and collaboration show positive influence on academic leadership practices and learning outcome. Seabi et al (2012), in a study on students' experiences about transformational leadership practices in a single South African university, found that teaching quality, academic support, material resources and teacher accessibility, all had a positive influence, while workload limited access to lecturers and learning materials had a negative impact on students' perception on transformational leadership practices of their lecturers. This implies that lecturers who are accessible and provide teaching and learning materials and deliver high quality lectures to students positively influenced them towards achieving their academic goals.…”
Section: Lecturers' Leadership Practices and Students' Participation mentioning
confidence: 99%